Penerapan Pengajaran Berdiferensiasi dalam Pembelajaran Fiqih bagi Siswa Berkebutuhan Khusus: Studi Kasus di MTS Genggong 2 - Fatimah, Siti; Susetya, Hemas Haryas Harja; Kurniawan, Rangga (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
In the learning process, every teacher faces different challenges. In order for learning to be carried out optimally, special methods are needed. This study will explain the application of Differentiated Instruction for students with special needs. The aim is to examine in depth the Differentiated Instruction method implemented at MTs Genggong 2. The method used in this study is descriptive, divided into four stages: subject and informant selection, data collection, data analysis, and validation. The results of this study indicate that the application of Differentiated Instruction for students with special needs at MTs Genggong is effective.